Trends and Impacts of Climate Change on the Livelihoods of Coastal Communities in North ‘A’ District, Zanzibar - Hamad, Ali; Sawe, Jackson (Tanzania Journal for Population studies and Development, 2022)
This article examines the trends and impacts of climate change on the livelihoods of coastal communities in Zanzibar. The study used both qualitative and quantitative research methodologies. Quantitative data was collected through household questionnaires, while qualitative data was collected through key informants interviews, focus group discussions, observations, and review of documents. Data on rainfall, temperature, and sea level pressure was acquired from the Tanzania Meteorological Authority (TMA) in Zanzibar. Moreover, remote sensing data of the medium-resolution Landsat 8 image was also used. Data was collected from 400 heads of household in the study area. Results show that most of the households admitted that there has been climate change as testified by rise in sea level, increase in temperature, and a decrease in the amount of rainfall. Moreover, the research findings indicate that climate change has affected coastal areas and the livelihoods of the community as a whole. Some of the impacts of climate change have been coastal erosion and destruction of agriculture and fishing activities. Therefore, it is concluded that climate change is a major environmental problem that affects people’s livelihood, especially for those with low adaptive capacity. It is recommended that strong measures be taken to address the problem of climate change. Furthermore, the government should facilitate the realization of global sustainable development goals by addressing the challenges brought forth by climate change through designing policies that aim to create solutions to climate change, and challenges faced in coastal communities such as Zanzibar.